Experiencia de investigación acción participativa (IAP) con estudiantes universitarios, para la difusión del legado de la Comisión de la Verdad de Colombia - Ruiz Echeverry, Piedad (2025)
The Final Report of the Truth Commission, presented to Colombians in 2022, is hosted on a transmedia platform that integrates written texts and multimedia products in various formats. This platform provides access to collected testimonies, analyses of the recovered truth, concrete data and figures on the multiple impacts of the armed conflict, and information about the social actors involved. The social appropriation of this report is an essential task in educational contexts, serving as a tool for ensuring non-repetition. Within this framework, a participatory action research process was conducted, generating initiatives such as the design of a communication strategy, recognition and awareness workshops, the collection of testimonies, the socialization of results, and the delivery of dissemination materials about the Commission’s Report.